Constructing a AZO/TiO2 Core/Shell Nanocone Array with Uniformly Dispersed Au NPs for Enhancing Photoelectrochemical Water Splitting. Issue 1 (5th November 2015) - Mi, Yan; Wen, Liaoyong; Xu, Rui; Wang, Zhijie; Cao, Dawei; Fang, Yaoguo; Lei, Yong
Abstract : Constructing core/shell nanostructures with optimal structure and composition could maximize the solar light utilization. Here, using an Al nanocone array as a substrate, a well‐defined regular array of AZO/TiO2 core/shell nanocones with uniformly dispersed Au nanoparticles (AZO/TiO2 /Au NCA) is successfully realized through three sequential steps of atomic layer deposition, physical vapor deposition, and annealing processes. By tuning the structural and compositional parameters, the advantages of light trapping and short carrier diffusion from the core/shell nanocone array, as well as the surface plasmon resonance and catalytic effects from the Au nanoparticles can be maximally utilized. Accordingly, a remarkable photoelectrochemical (PEC) performance can be acquired and the photocurrent density of the AZO/TiO2 /Au NCA electrode reaches up to 1.1 mA cm −2 at 1.23 V, versus reversible hydrogen electrode (RHE) under simulated sunlight illumination, which is five times that of a flat AZO/TiO2 electrode (0.22 mA cm −2 ). Moreover, the photoconversion of the AZO/TiO2 /Au NCA electrode approaches 0.73% at 0.21 V versus RHE, which is one of the highest values with the lowest applied bias ever reported in Au/TiO2 PEC composites. These results demonstrate a feasible route toward the scalable fabrication of well‐modulated core/shell nanostructures and can be easily applied to other metal/semiconductor composites for high‐performance PEC. Abstract : The construction of core/shell nanocones with optimal structure and composition can maximize solar light utilization. A well‐defined, regular array of AZO/TiO2 core/shell nanocones with uniformly dispersed Au nanoparticles (NPs) is successfully realized. By tuning each parameter of the photoelectrode, the photoconversion approaches 0.73% at 0.21 V versus the reversible hydrogen electrode, which is one of the highest values with the lowest applied bias ever reported in Au/TiO2 photoelectrochemical composites.